STUDENTS’ ABILITY IN DIFFERENTIATING PRESENT CONTINUOUS TENSE AND GERUND OF THE FOURTH SEMESTER STUDENTS AT FKIP UKI TORAJA - Viktor Siumarlata (English Language Teaching Methodology, 2022)
The problem statements are formulated as follows: to what extent is the student's ability to differentiate between the present continuous tense and the gerund of the fourth semester students at FKIP UKI Toraja? In this research, the researcher used the quantitative method. The participants of this research were fourth semester students at FKIP UKI Toraja. To collect the data, the researcher used a written test in the form of multiple choice. The researcher took 20 students to Campus 1. The research results finally extended the conclusion that the answer to the research question about the ability of the fourth semester students of FKIP UKI Toraja in differentiating present continuous tense and gerund, the researcher concludes that the ability of the fourth semester students of FKIP UKI Toraja in differentiating present continuous tense and gerund, falls into the failed category.shown by the mean score of 41.4.